DIAGNOSTIC ASPECTS OF PERSISTENT PULMONARY HYPERTENSION IN PREMATURE INFANTS WITH OXIDATIVE STRESS - Т. Клименко; M. Кононович (Неонатологія, хірургія та перинатальна медицина, 2022)
Introduction. Persistent pulmonary hypertension is a problem that leads to high morbidity and mortality in preterm infants. In clinical studies, oxidative stress (OS) contributes to the development of pulmonary hypertension (PH). The most specific biomarker of OS in preterm infants is urinary 8-hydroxy-2-deoxyguanosine (8-OHdG). The aim of the study. To determine the clinical and diagnostic relationship between the value of 8-hydroxy-2- deoxyguanosine and the level of mean trunk pulmonary artery pressure in premature infants with respiratory distress syndrome and asphyxia in the early neonatal period. Material and methods. Determination of 8-OHdG (ng/ml) by enzyme-linked immunosorbent assay (ELISA) and PH by echocardiography (EchoCG) in 60 premature infants at 26-32 weeks of gestation at 1 and 3-5 days of life in 2 groups: I - 32 children with respiratory distress syndrome (RDS); II - 28 children with RDS in combination with perinatal asphyxia. Results. The average value of pulmonary artery pressure (mmHg) in the group II of children in comparison with group I was higher both in 1 and 3-5 days of life. The level and dynamics of 8-OHdG correlated with the severity of PH, which required longer respiratory support in group II. Sexual dimorphism of 8-OHdG levels and dynamics was noted. Conclusions. Perinatal asphyxia in preterm infants with RDS on the 1st day of life complicates the course of PH, as indicated by a higher level of the urinary 8-OHdG and correlated to mPAP. Gender characteristics of the dynamics of 8-OHdG levels in children with perinatal pathology reveal reduced adaptability and reactivity of boys to OS at birth. Dynamics in the form of a decrease in the level of 8-OHdG in the urine is a favorable prognostic sign of pulmonary hypertension. Gender characteristics of the dynamics of 8-OHdG levels in children with perinatal pathology reveal reduced adaptability and reactivity of boys to OS at birth.